Perancangan Sistem Informasi Jasa Wedding Organizer pada CV. Boganesia Jaya Berbasis Web - Difia Agustin; Alexius Ulan Bani; Fauziyah (Jurnal Jaring SainTek, 2020)
The presence of technology and science has evolved in the world of work and its development, in this Globalization Era, it requires people to participate in these developments. This method uses processing in the field of work which was initially managed manually by recording orders written in a ledger, now managed using modern technology. From the results of this study it can be seen that in recording existing orders on the CV. Boganesia Jaya has not implemented the system or is still using manual methods. In that case some suggestions can be given to the company for further development by means of an information system designed using an application with the web-based PHP and MySQL programming language to solve this problem in CV. Boganesia Jaya which is more effective and accurate.